1999
DOI: 10.1002/(sici)1521-4141(199901)29:01<284::aid-immu284>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the response of naive and memory CD8 T cells to antigen: similarities and differences

Abstract: We have studied the kinetics of the antigen induced response of naive and memory CD8 T cells expressing a transgenic T cell receptor (TCR) specific for the glycoprotein peptide amino acid 33-41 (GP33) of the lymphocytic choriomeningitis virus (LCMV). Memory T cells were generated in vivo by adoptive transfer of LCMV TCR transgenic T cells into normal recipient mice, followed by LCMV infection. The results demonstrated that the cell cycle progression and kinetics of TCR down-modulation, CD25 and CD69 up-regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
96
0
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(117 citation statements)
references
References 26 publications
(26 reference statements)
18
96
0
3
Order By: Relevance
“…However, the fact that Ag-loaded DC were present in the DLN of naive TCR transgenic mice at 16 h and then were lost by 72 h is highly suggestive of a cytolytic mechanism operating within the node. Furthermore, the kinetics of DC clearance in naive animals are consistent with the reported time required for CTL to gain cytolytic function upon activation (20,25). Preliminary experiments indicated that DC clearance is not impaired in IFN-␥-deficient mice (data not shown), suggesting that this cytokine is not critical to the clearance process and that other effector mechanisms, presumably cytotoxicity, have a greater role.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the fact that Ag-loaded DC were present in the DLN of naive TCR transgenic mice at 16 h and then were lost by 72 h is highly suggestive of a cytolytic mechanism operating within the node. Furthermore, the kinetics of DC clearance in naive animals are consistent with the reported time required for CTL to gain cytolytic function upon activation (20,25). Preliminary experiments indicated that DC clearance is not impaired in IFN-␥-deficient mice (data not shown), suggesting that this cytokine is not critical to the clearance process and that other effector mechanisms, presumably cytotoxicity, have a greater role.…”
Section: Discussionsupporting
confidence: 92%
“…The effect of Ag presented on MHC class I on DC survival in the DLN was also examined. We show that Ag-loaded DC disappear from the lymph node during the course of a CD8 ϩ T cell response, with kinetics that parallel the known kinetics of activation of CD8 ϩ T cells to effector function (20,25). Ag-loaded DC were immediately cleared in recently immunized mice with a reduction in DC numbers observed in the DLN within 20 h of injection, suggesting that some DC may have been eliminated before reaching the lymph node.…”
Section: Discussionmentioning
confidence: 99%
“…Positive control stimulations were carried out using 2.5 g/ml Staphylococcus aureus enterotoxin B (SEB; Sigma, Deisenhofen, Germany) or titered amounts of antigen derived from adenovirusinfected cells (BioWhittaker) as described previously (20). Cells were incubated in polypropylene tubes at 37°C at 6% CO 2 for a total of 6 h. During this time, effector and memory CD4 and CD8 T cells are specifically stimulated, resulting in the upregulation of CD69 and the production of cytokines (19,21). During the last 4 h, 10 g/ml of Brefeldin A (Sigma) was added to block extracellular transport of cytokines.…”
Section: Stimulation Of Cmv-specific Cd4 and Cd8 T Cells Within Wholementioning
confidence: 99%
“…La plupart des études montrent que les lymphocytes T CD8 + mémoire produisent davantage de cytokines effectrices et plus rapidement que les lymphocytes T CD8 + naïfs, après stimulation par l'antigène in vitro [9,14]. En revanche, selon les modèles, elles présentent des capacités proliféra-tives accrues [9,12,15], identiques [10,16] ou diminuées [13] lorsqu'on les compare aux lymphocytes T CD8 + naïfs. Dans un autre modèle transgé-nique, les lymphocytes T CD8 + mémoire ne prolifèrent pas du tout lors d'une re-stimulation par l'antigène in vitro [11].…”
Section: Diversité Des Populations De Lymphocytes Mémoire T Cd8 +unclassified
“…Dans un autre modèle transgé-nique, les lymphocytes T CD8 + mémoire ne prolifèrent pas du tout lors d'une re-stimulation par l'antigène in vitro [11]. De même, dans certains systèmes, mais pas d'autres [10], les lymphocytes T CD8 + mémoire montrent des activités cytolytiques ex vivo, en l'absence de re-stimulation [11,13] (Tableau II). Cependant, il faut noter que, chez la souris, la population de cellules CD44 high est elle-même hétérogène.…”
Section: Diversité Des Populations De Lymphocytes Mémoire T Cd8 +unclassified